Screening for inter-hospital differences in cesarean section rates in low-risk deliveries using administrative data: An initiative to improve the quality of care - Verstraelen Hans; Molenberghs Geert; Windey Francis; Aelvoet Willem; Van Reempts Patrick; Foidart Jean-Michel (BMC, 2008)
Abstract Background Rising national cesarean section rates (CSRs) and unexplained inter-hospital differences in CSRs, led national and international bodies to select CSR as a quality indicator. Using hospital discharge abstracts, we aimed to document in Belgium (1) inter-hospital differences in CSRs among low risk deliveries, (2) a national upward CSR trend, (3) lack of better neonatal outcomes in hospitals with high CSRs, and (4) possible under-use of CS. Methods We defined a population of low risk deliveries (singleton, vertex, full-term, live born, <4500 g, >2499 g). Using multivariable logistic regression techniques, we provided degrees of evidence regarding the observed departure ([relative risk-1]*100) of each hospital (N = 107) from the national CSR and its trend. To determine a benchmark, we defined three CSR groups (high, average and low) and compared them regarding 1 minute Apgar scores and other neonatal endpoints. An anonymous feedback is provided to the hospitals, the College of Physicians (with voluntary disclosure of the outlying hospitals for quality improvement purposes) and to the policy makers. Results Compared with available information, the completeness and accuracy of the data, regarding the variables selected to determine our study population, showed adequate. Important inter-hospital differences were found. Departures ranged from -65% up to +75%, and 9 "high CSR" and 13 "low CSR" outlying hospitals were identified. We observed a national increasing trend of 1.019 (95%CI [1.015; 1.022]) per semester, adjusted for age groups. In the "high CSR" group 1 minute Apgar scores < 4 were over-represented in the subgroup of vaginal deliveries, suggesting CSs not carried out for medical reasons. Under-use of CS was also observed. Given their questionable completeness, except Apgar scores, our neonatal results, showing a significant association of CS with adverse neonatal endpoints, are to be cautiously interpreted. Taking the available evidence into account, the "Average CSR" group seemed to be the best benchmark candidate. Conclusion Rather than firm statements about quality of care, our results are to be considered a useful screening. The inter-hospital differences in CSR, the national CS upward trend, the indications of over-use and under-use, the geographically different obstetric patterns and the admission day-related concentration of deliveries, whether or not by CS, may trigger initiatives aiming at improving quality of care.